2017
DOI: 10.1002/jrs.5135
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Raman‐active crystals as a narrowband probe light source for picosecond three‐color vibrational CARS thermometry

Abstract: The feasibility of N2‐based vibrational three‐color coherent anti‐Stokes Raman scattering (CARS) thermometry employing narrowband stimulated Raman scattering (SRS) of a picosecond pump laser pulse in a Raman‐active crystal to provide the wavelength‐shifted probe radiation has been investigated. This shift of the probe beam wavelength is aimed to enable temperature measurements in sooting flames by using the established technique of N2 vibrational CARS spectroscopy in the range free from the interference of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The comparative study of the employment of two high SRS gain Raman‐active crystal materials, namely, Ba (NO 3 ) 2 and KGd (WO 4 ) 2 , pumped by a 100‐ps frequency‐doubled Nd:YAG laser pulse was performed. Despite the comparable conversion efficiencies into the first‐order Stokes SRS radiation provided by both crystals, the achievable pulse energies were four to five times larger for the KGd(WO 4 ) 2 crystal, and the vibrational CARS spectra at flame temperatures had a significantly better signal‐to‐noise ratio . Park et al described the authentication of adulterated edible oil using CARS spectroscopy.…”
Section: Nonlinear Coherent and Time‐resolved Raman Spectroscopymentioning
confidence: 95%
See 1 more Smart Citation
“…The comparative study of the employment of two high SRS gain Raman‐active crystal materials, namely, Ba (NO 3 ) 2 and KGd (WO 4 ) 2 , pumped by a 100‐ps frequency‐doubled Nd:YAG laser pulse was performed. Despite the comparable conversion efficiencies into the first‐order Stokes SRS radiation provided by both crystals, the achievable pulse energies were four to five times larger for the KGd(WO 4 ) 2 crystal, and the vibrational CARS spectra at flame temperatures had a significantly better signal‐to‐noise ratio . Park et al described the authentication of adulterated edible oil using CARS spectroscopy.…”
Section: Nonlinear Coherent and Time‐resolved Raman Spectroscopymentioning
confidence: 95%
“…Despite the comparable conversion efficiencies into the first-order Stokes SRS radiation provided by both crystals, the achievable pulse energies were four to five times larger for the KGd(WO 4 ) 2 crystal, and the vibrational CARS spectra at flame temperatures had a significantly better signal-to-noise ratio. [105] Park et al described the authentication of adulterated edible oil using CARS spectroscopy. In this work, they showed that CARS spectroscopy can be used as a method of authentication of adulterated edible oil by demonstrating a method to determine the type and the amounts of unknowns in mixed oil.…”
Section: Coherent Anti-stokes Raman Spectroscopy (Cars)mentioning
confidence: 99%
“…Some of these states were observed and studied for the very first time. Meißner et al carried out a feasibility study on the use of a Raman‐active crystal in picosecond‐CARS of nitrogen. The Raman crystal facilitated narrowband stimulated Raman scattering (SRS) to produce a coherent beam for three‐color CARS thermometry.…”
mentioning
confidence: 99%